The role of the institution in choosing, receiving and chaperone professors in the university - Marques Ferreira, Maria de Lourdes da Silva (Investigación y Educación en Enfermería, 2011)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To analyze the role of the institution in choosing, receiving and chaperone professors. Methodology. Qualitative study, which body analysis was composed of 32 participations in a thematic forum of a group of nine health professionals. Results. After professor hiring it is necessary to receive and chaperone him. Professors with longer time in the institution represent a more important role in the admission of the new professor. Chaperone process is an opportunity to change and redefine the rules, and should be supported by permanent evaluation. The university as a legitimate learning scenario, production and knowledge reconstitution, should accompany changes of contemporary science and support the interdisciplinary demands in the new knowledge construction. Conclusion. It is fundamental the role of the university receiving and chaperoning teachers from joining. As well university should favor the growth of the professor, not only by supporting the challenges of their pedagogic activity, but mainly through the respect of autonomy.